Identifying challenges in crowdfunded product development: a review of Kickstarter projects. (23rd October 2018) - Jensen, Lasse Skovgaard; Özkil, Ali Gürcan
Abstract : This paper provides an empirical review of the reward-based crowdfunding platformKickstarter.com, with the aim to explore and identify challenges in crowdfunded product development, which consequently can lead to failure of the crowdfunding campaign. The review was based on the analysis of a total of 144 successfully funded 'technology' campaigns, which all concerned the creation of physical consumer hardware preordered by campaign backers. The analysis was built around a failure mode model, which was established through a pre-study. The study reveals that (i) no more than 32% of the campaigns managed to deliver the crowdfunded products on time, and, if campaigns are delayed, (ii) there is a significantly higher probability that the delivered products might lack expected attributes. The causes for delay have many reasons, but (iii) a set of particular product development issues were identified as the main challenges. A better understanding of crowdfunded product development can help researchers and practitioners to better understand and utilize the opportunities of this new product development paradigm.